Impact of Serum Uric Acid Levels on Outcomes following Renal Artery Revascularization in Patients with Renovascular Disease. (30th January 2019) - Chen, Xiao-jun; Eirin, Alfonso; Kane, Garvan C.; Misra, Sanjay; Textor, Stephen C.; Lerman, Amir; Lerman, Lilach O.
Abstract : Background . Percutaneous transluminal renal angioplasty (PTRA) improves blood pressure (BP) and renal function only in selected patients with atherosclerotic renovascular disease (ARVD). Hyperuricemia is associated with elevated risk for hypertension and chronic renal disease, but its role in renovascular hypertension is unclear. We hypothesized that hyperuricemia negatively impacts renal and BP outcomes among patients with ARVD undergoing PTRA. Methods . This retrospective, observational cohort study included 94 patients with ARVD and preserved systolic cardiac function, who underwent PTRA at Mayo Clinic, Rochester, Minnesota. Renal, BP, and mortality outcomes were compared among patients according to their serum uric acid (SUA) levels. Multivariate analysis was used to determine significant predictors of renal, BP, and mortality outcomes after PTRA. Results . Compared to patients with normal basal SUA levels (≤5.7 mg/dl), patients with very high SUA (≥8.7 mg/dl) had lower baseline estimated glomerular filtration rate (eGFR), more extensive use of antihypertensive and diuretic drugs, increased baseline systolic blood pressure (SBP), and elevated left ventricular mass index. After PTRA, multiple logistic regression analysis showed that, compared to normal SUA, very high SUA was associated with decreased odds ratio (OR) of change in eGFR (adjusted OR=0.90; 95% confidence interval [CI], 0.86-0.95), but not of change in SBP. In multivariate linear analysis SUA independently predicted delta urine protein/creatinine ratio ( β : 26.0; 95% confidence interval, 13.9 to 38.1). Conclusion . Severe hyperuricemia in patients with AVRD may have a negative impact on outcomes of renal revascularization.